CONTRIBUTION OF ARGUMENTATATIVE PARAGRAPH TOWARD STUDENT'S WRITING SKILL OF INDONESIAN EDUCATION STUDENTS (KONTRIBUSI PARAGRAF ARGUMENTASI TERHADAP KETERAMPILAN MENULIS MAHASISWA PENDIDIKAN BAHASA INDONESIA) - Hidayati Azkiya; Romi Isnanda (Jurnal Gramatika, 2020)
The purpose of this study was to determine the contribution of knowledge paragraphs to the writing skills of argumentation. Because at the moment it looks that the knowledge of Grammar or paragraph less attention in writing. Though good writing was also seen from Grammar or knowledge of the paragraphs is good also. While the argument writing skills, students are still difficulties in providing opinions or opinions and Actual phenomena occurring at present. This research method using a descriptive correlational design. This study population is students of Indonesian Education 20016/2017 BP totaling 30 people. Based on the research that the average knowledge of the paragraph is 32.25. And the contribution of knowledge to the writing skills of argument paragraph by 12%. It can be concluded that the knowledge paragraphs affect student writing skills arguments the Indonesian Education Studies Program University of Bung Hatta, but knowledge of the paragraph is very less seen than the class average.